Faktor-faktor yang Mempengaruhi Kepuasan Konsumen Terhadap Beras Merah Organik di Kota Denpasar - JESSY VENY OMBUN SIANTURI; I GEDE SETIAWAN ADI PUTRA; WAYAN GINARSA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT Factors Affecting Consumer Satisfaction Of Organic Red Rice in Denpasar This study aims to find the factors that affect customer satisfaction with organic brown rice in Denpasar and know the level of customer satisfaction with organic brown rice consumed in Denpasar. The research was conducted in Denpasar which took place in two places, gods Tiara Supermarkets and health food stores